Inger Johanne's lively doings - Zwilgmeyer, Dikken, 1853-1913; Young, Florence Liley, 1872-1974; Poulsson, Emilie, 1853-1939 (Salt Lake City, UT : Project Gutenberg, 2023)
"Inger Johanne's Lively Doings" by Dikken Zwilgmeyer is a children's novel written in the early 20th century. The story follows the spirited adventures of a young girl named Inger Johanne, who delights in recounting her experiences in a charming Norwegian town filled with both mundane and whimsical occurrences, alongside her friends and family. At the start of the book, Inger Johanne introduces herself and humorously reflects on her unexpected success as an author, sharing how her first book was received. She explains her desire to write about the lively happenings in her town, and she describes some mischievous antics involving her brother Karsten and their friends. Their adventures set the tone for a delightful narrative filled with youthful exuberance, friendship, and the innocence of childhood, all while exploring the enchanting dynamics of their everyday lives. (This is an automatically generated summary.)
Release date is 2023-03-12
Bob Taylor, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Girls -- Juvenile fiction; Norway -- Juvenile fiction